2010
DOI: 10.4049/jimmunol.1001036
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ Regulatory T Cells Prevent Type 1 Diabetes Preceded by Dendritic Cell-Dominant Invasive Insulitis by Affecting Chemotaxis and Local Invasiveness of Dendritic Cells

Abstract: Development of type 1 diabetes (T1D) is preceded by invasive insulitis. Although CD4+CD25+ regulatory T cells (nTregs) induce tolerance that inhibits insulitis and T1D, the in vivo cellular mechanisms underlying this process remain largely unclear. Using an adoptive transfer model and noninvasive imaging-guided longitudinal analyses, we found nTreg depletion did not affect systemic trafficking and tissue localization of diabetogenic CD4+ BDC2.5 T (BDC) cells in recipient mice prior to development of T1D. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…CCL5 levels are elevated in serum of type 1 diabetic patients and contribute to the attraction of monocytes and neutrophils to the islets during insulitis [41,42]. CCL19 levels are also increased during diabetes development and enhance the migration of dendritic cells and macrophages to the islets [43,44]. CXCL12 levels are elevated in type 1 diabetes, and CXCL12 contributes to insulitis by stimulating the trafficking and homing of autoreactive B and T cells in animal models of type 1 diabetes [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…CCL5 levels are elevated in serum of type 1 diabetic patients and contribute to the attraction of monocytes and neutrophils to the islets during insulitis [41,42]. CCL19 levels are also increased during diabetes development and enhance the migration of dendritic cells and macrophages to the islets [43,44]. CXCL12 levels are elevated in type 1 diabetes, and CXCL12 contributes to insulitis by stimulating the trafficking and homing of autoreactive B and T cells in animal models of type 1 diabetes [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the change in cellular components in the islets may be due to the nTreg cells' ability to regulate the local migration of immune cells. In studies to address these questions, we found that, compared to that in control nTreg cell-sufficient mice, the accelerated invasive insulitis in nTreg cell-deficient recipient NOD/scid mice was predominated by a population of CD11c + dendritic cells, instead of by the adoptively transferred CD4 + BDC T cells (Lee et al, 2010). These results suggest that the presence of nTreg cells may inhibit islet-infiltration of CD11c + dendritic cells.…”
Section: Application Of Bli To Understand the Role Of Ntreg Cells In mentioning
confidence: 72%
“…These studies showed that depletion of nTreg cells promoted progression and increased severity of insulitis in nTreg cell-deficient mice. Therefore, nTreg cell-deficient mice developed more severe invasive insulitis, compared to mostly periinsulitis found in control nTreg cell-sufficient mice (Lee et al, 2010). However, despite these differences, the nTreg cell-deficiency did not affect the number and activation status of BDC cells during the pre-diabetic stage.…”
Section: Application Of Bli To Understand the Role Of Ntreg Cells In mentioning
confidence: 73%
See 2 more Smart Citations